Mechatronis: The Output Energy of MEMS Explosive Train. Issue 2 (March 2021) - Tan, Ming; Zhang, Liang; Zeng, Xiangtao; Xia, Wen
Abstract: A micron scale of microelectromechanical systems (MEMS) explosive train with applications in both space exploration and electronic control of safety airbag, the MEMS explosive train is designed to shock initiate a linear shaped charge by accelerating a thin metal plate across a small gap. This paper summarizes the experiment results of Φ0.9×0.6mm micro-charge driven different thickness flyer's velocity by Photonic Doppler Velocimetry (PDV), compared to the calculation result of Gurney formulation, the flyer's velocity of micro-charge driven different thickness lower than the calculation. The velocity-time variation curve and the energy variation with distance provide some information available for micro-explosive train design.